BCG Moreau Polish Substrain Infections in Patients With Inborn Errors of Immunity: 40 Years of Experience in the Department of Immunology, Children's Memorial Health Institute, Warsaw - Bernatowska, Ewa; Pac, Małgorzata; Heropolitańska-Pliszka, Edyta; Pietrucha, Barbara; Dąbrowska-Leonik, Nel; Skomska-Pawliszak, Małgorzata; Bernat-Sitarz, Katarzyna; Krzysztopa-Grzybowska, Katarzyna; Wolska-Kuśnierz, Beata; Bohynikova, Nadia; Augustynowicz, Ewa; Augustynowicz-Kopeć, Ewa; et al. (Frontiers in Pediatrics, 2022)
Abstract Objective To assess BCG complications in patients with Inborn Errors of Immunity (IEI), according to the inherited disorders and associated immunological defects, as well as the different BCG substrains. Material Study design adverse reactions to the locally-produced BCG Moreau vaccine were analyzed in IEI patients, diagnosed between 1980 and 2020 in the Department of Immunology, Children’s Memorial Health Institute (CMHI), Warsaw. These results were compared with previously published studies. Results Significantly fewer disseminated BCG infections (BCGosis) were found in 11 SCID patients, only with NK - phenotype out of 72, 15%, when compared with 119 out of 349, 34% (p = 0.0012) SCID patients vaccinated with BCG in other countries. Significantly fewer death caused by BCGosis was observed (p = 0.0402 ). A significantly higher number of hematopoietic stem cells transplantations (HSCT) were performed in the CMHI study (p = 0.00001). BCGosis was found in 6 patients with Mendelian susceptibility to mycobacterial diseases (MSMD). Other IEI prone to BCG complication, such as CGD, showed no case of BCGosis. Conclusion The BCG Moreau substrain vaccine produced in Poland since 1955 has genetic differences with its parental Brazilian substrain, together with a superior safety clinical profile in comparison with the other BCG substrains, with no BCGosis in patients with IEI other than SCID and MSMD. Our data also confirmed significantly fewer cases of BCGosis and deaths caused by BCG infection in SCID patients with this vaccine substrain. Finally, they confirmed the protecting role of NK cells, probably via their production of IFNgamma.